2014
DOI: 10.1128/jcm.02934-13
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus suis-Related Prosthetic Joint Infection and Streptococcal Toxic Shock-Like Syndrome in a Pig Farmer in the United States

Abstract: e Streptococcus suis is an emerging swine-associated zoonotic agent that can cause meningitis and septicemia in humans. We present, to our knowledge, the first case of S. suis arthroplasty infection and streptococcal toxic shock-like syndrome due to an nonencapsulated serotype 5 strain in North America. CASE REPORTA 74-year-old man with a history of non-Hodgkin's lymphoma, in remission, and splenectomy was transferred to our institution for management of septic shock. The patient was a pig farmer who had under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Misidentification of S. suis is very common: this bacterium is frequently misidentified as Streptococci viridans [14] and has also been misidentified as Streptococcus bovis, Streptococcus pneumoniae, Streptococcus faecalis, and Streptococcus acidominimus [2,6,21,83]. Misidentification of S. suis also has been reported in Canada, which raises suspicion that human S. suis infections might be underdiagnosed in North America [84,85]. In the report by Tarini et al, a previously healthy 50-year-old man was admitted to one of the district hospitals in Bali Province, Indonesia, due to meningitis.…”
Section: Discussion and Review Of European Literaturementioning
confidence: 99%
“…Misidentification of S. suis is very common: this bacterium is frequently misidentified as Streptococci viridans [14] and has also been misidentified as Streptococcus bovis, Streptococcus pneumoniae, Streptococcus faecalis, and Streptococcus acidominimus [2,6,21,83]. Misidentification of S. suis also has been reported in Canada, which raises suspicion that human S. suis infections might be underdiagnosed in North America [84,85]. In the report by Tarini et al, a previously healthy 50-year-old man was admitted to one of the district hospitals in Bali Province, Indonesia, due to meningitis.…”
Section: Discussion and Review Of European Literaturementioning
confidence: 99%
“…Although serotype 2 is the most prevalent type recovered from humans, zoonotic cases involving serotypes 1, 4, 5, 14, 16, 21 and 24 have also been reported [ 1 , 5 , 8 , 12 , 13 , 15 ], with serotypes 5 and 24 being the most recently reported cases in Thailand [ 12 ]. Serotype 5 strains have also been isolated from humans in U.S.A. and Europe [ 7 , 8 ]. Serotypes 4 and 5 were identified in our study, and their numbers were similar to those found for serotype 2, suggesting their long-term existence in this area and their potential to cause disease in both swine and humans.…”
mentioning
confidence: 99%
“…The strain isolated from this case belonged to ST221 in CC221/234. To the best of our knowledge, only two other unencapsulated strains have been recovered from human cases [ 3 , 34 ], although unencapsulated S. suis has frequently been isolated from pigs [ 1 , 35 ]. It is particularly interesting that CC221/234 did not contain any serotype 2 strains, but rather only serotype 24 strains (ST221 and ST234) ( http://ssuis.mlst.net/sql/burstspadvanced.asp ).…”
Section: Discussionmentioning
confidence: 99%